Gejolak Pemikiran Dua Tokoh Indonesia 1fasa Revolusi Kemerdekan (studi Kasus Sutan Sjahrir dan Tan Malaka) - Rizal, Anton Niyus (Pendidikan Sejarah, 2014)
Â The leaders of the nattonal movement have dtfferent vtews dependtng on the duecoon of chotce fight for Indonesian independence proclaimed. In stmple terms the political eltte and the nauonalleadershtp of the movement when it was split into those who agree ad choose the path of diplomacy (negotiate) as Sjahrir-Amir Sjanfuddin and they were reJected because the lines beheves dtplomacy wtll only hurt the Indonesian revolution ,the choose the path of physical struggle (armed) struggle for suggesting the model armed most profitable Indonesian revolution . It can be said the Tan Malaka-Sudirman and radical youth groups tncludtng those that support the lines ofthts struggle The purpose of this thesis to describe and analyze the thought of two figures whteh move lndonestan Sutan Sjahns and Tao Malaka in an effort to maintatn the independence of Indonesian. The method used in this paper is a this method emphast.ZeS the attempt to equate the facts so they can achteve a lia1son mterstJce facts, givmg meaJung to the entire events of the post to be achteved through a heuristic pmcedure,source cnticism, interpretation, and histonography. Difference model of the struggle to defend the group into two parties fight against each other, e between groups With the concept of diplomacy and government opposillon to the concept of revolution the differences of op1mon on the hand posibve tmpact, but on the other hand also 1mpact negative for the success of the course of the revolution Indonesian